2020
DOI: 10.1109/te.2019.2926054
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Systems Engineering Course in Developing Systems Thinking

Abstract: Contribution: An evaluation of the effectiveness of Systems Engineering (SE) courses in developing students' Systems Thinking (ST) capacity in both the cognitive and affective domains. A combined cognitive ST performance and affective engagement with ST assessment is proposed as an approach to assess students' ST in both domains. The results can support course change decisions and guide learning experience development. Background: SE education aims to produce graduates with strong knowledge and skills in SE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, the current version of the student survey should be modified to increase the sensitivity of the measurement tool for changes in student attitudes, knowledge, and perceptions. A prominent option is to implement the Student Assessment of their Learning Gains (SALG) online instrument of [33] with considerations and validation methods discussed by [36] and [37].…”
Section: General Discussion: Lessons Learned and Future Workmentioning
confidence: 99%
“…Thus, the current version of the student survey should be modified to increase the sensitivity of the measurement tool for changes in student attitudes, knowledge, and perceptions. A prominent option is to implement the Student Assessment of their Learning Gains (SALG) online instrument of [33] with considerations and validation methods discussed by [36] and [37].…”
Section: General Discussion: Lessons Learned and Future Workmentioning
confidence: 99%
“…The cognitive domain introduced in Bloom's taxonomy is a hierarchical structure consisting of the aforesaid six levels. In present days more and more importance is given to outcome-based learning systems [10][11][12] for the overall growth of a student and for the all-round development from understanding a topic and to the extent of applying the gathered knowledge to design a new model or concept. Nowadays, the online mode of education is gaining popularity for its effectiveness and recent research studies have demonstrated their encouraging effect on achieving learning outcomes [13].…”
Section: Introductionmentioning
confidence: 99%